Identifikasi Morfologi Mikroorganisme Lokal (Mol) Isi Rumen Sapi dengan Supply Energi yang Berbeda - tri astuti; Delsi Afrini; Alfian Asri (Jurnal Peternakan Mahaputra, 2021)
This study aims to make a morphological identification of the rumen contents of moles given a different source of glucose as an energy supply for microorganisms contained in Mol solution. In the process of making moles, it is also compared to aerobically and anaerobically. There are six types of moles which are made from the contents of the rumen with different compositions, namely: 1. Rumen contents + molasses + tofu water anaerobically, 2. Rumen liquid + molasses + soaked soybean aerobically, 3.1 rumen content + rice water + molasses an aerobically, 4. Fill the rumen + sugar + soybean water. The four mixtures of local microorganisms were incubated for 7 days. The results of the microbial identification observations were discussed descriptively. Based on the results of microbial identification, there are types of bacteria bacillus sp, and the fungus Candida sp.